Protective role of the CD73-A2AR axis in cirrhotic cardiomyopathy through negative feedback regulation of the NF-κB pathway - Zhao, Ning; Shao, Zhenhao; Xia, Guoqing; Liu, Huanhuan; Zhang, Lei; Zhao, Xiaoxi; Dang, Shipeng; Qian, Lingling; Xu, Wentao; Yu, Zhiming; Wang, Ruxing (Frontiers in Immunology, 2024)
Background: Myocardial inflammation and apoptosis induced by cirrhosis are among the primary mechanisms of cirrhotic cardiomyopathy. CD73, a common extracellular nucleotidase also known as 5'-nucleotidase, is associated with the progression of inflammation and immunity in multiple organs. However, the mechanism by which CD73 contributes to myocardial inflammation and apoptosis in cirrhosis remains unclear.In this study, a cirrhotic cardiomyopathy model in mice was established by bile duct ligation.Myocardial-specific overexpression of CD73 was achieved by tail vein injection of AAV9 (adeno-associated virus)-cTNT-NT5E-mCherry, and cardiac function in mice was assessed using echocardiography. Myocardial inflammation infiltration and apoptosis were evaluated through pathological observation and ELISA assays. The expression of CD73, A2AR, apoptotic markers, and proteins related to the NF-κB pathway in myocardial tissue were measured.In the myocardial tissue of the cirrhotic cardiomyopathy mouse model, the expression of CD73 and A2AR increased. Overexpression of CD73 in the myocardium via AAV9 injection and stimulation of A2AR with CGS 21680 inhibited myocardial inflammation and cardiomyocyte apoptosis induced by cirrhosis. Additionally, overexpression of CD73 suppressed the activation of the NF-κB pathway by upregulating the expression of the adenosine receptor A2A.Our study reveals that the CD73/A2AR signaling axis mitigates myocardial inflammation and apoptosis induced by cirrhosis through negative feedback regulation of the NF-κB pathway.